1990
DOI: 10.1126/science.2305266
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Suprachiasmatic Nucleus Determines Circadian Period

Abstract: The pacemaker role of the suprachiasmatic nucleus in a mammalian circadian system was tested by neural transplantation by using a mutant strain of hamster that shows a short circadian period. Small neural grafts from the suprachiasmatic region restored circadian rhythms to arrhythmic animals whose own nucleus had been ablated. The restored rhythms always exhibited the period of the donor genotype regardless of the direction of the transplant or genotype of the host. The basic period of the overt circadian rhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
819
0
27

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,603 publications
(876 citation statements)
references
References 23 publications
17
819
0
27
Order By: Relevance
“…Compelling evidence for a diffusible output signal derives from neural tissue transplantations in which the SCN from a fetal donor is implanted into the third ventricle of an adult, SCN-lesioned host. As mentioned previously, these grafts restore activity-related behaviors such as locomotor, drinking, and gnawing rhythms (Lehman et al, 1987;Ralph et al, 1990;Silver et al, 1990). That a diffusible signal is sufficient to restore locomotor rhythmicity in SCN-lesioned hosts was demonstrated by encapsulating donor SCN tissue in a membrane that prevented neural outgrowth while allowing the diffusion of signals between graft and host (Silver et al, 1996).…”
Section: Circadian Output and Orchestration Of Endocrine Function Difmentioning
confidence: 80%
See 1 more Smart Citation
“…Compelling evidence for a diffusible output signal derives from neural tissue transplantations in which the SCN from a fetal donor is implanted into the third ventricle of an adult, SCN-lesioned host. As mentioned previously, these grafts restore activity-related behaviors such as locomotor, drinking, and gnawing rhythms (Lehman et al, 1987;Ralph et al, 1990;Silver et al, 1990). That a diffusible signal is sufficient to restore locomotor rhythmicity in SCN-lesioned hosts was demonstrated by encapsulating donor SCN tissue in a membrane that prevented neural outgrowth while allowing the diffusion of signals between graft and host (Silver et al, 1996).…”
Section: Circadian Output and Orchestration Of Endocrine Function Difmentioning
confidence: 80%
“…The initial conclusion that the SCN serves as a brain master clock has been confirmed in the subsequent 30 years by converging lines of research involving in vivo, ex vivo, and in vitro studies carried out in many different laboratories. For example, transplants of donor SCN tissue into the brains of arrhythmic, SCN-lesioned hosts restore circadian rhythmicity in behavior (Lehman et al, 1987;Ralph et al, 1990). Importantly, rhythms are restored with the period of the donor SCN, indicating that the transplanted tissue does not act by restoring host brain function but that the "clock" is contained in the transplanted tissue.…”
Section: Identification Of a Brain "Clock": From Tissue To Genementioning
confidence: 99%
“…The SCN is the primary circadian pacemaker determining the period of circadian locomotor activity rhythms (Ralph et al, 1990). DAT-KD mice are characterized by elevated DA levels (Zhuang et al, 2001), and the SCN expresses D1 receptors.…”
Section: Elevated Dopamine Signaling Lengthened Circadian Period By Amentioning
confidence: 99%
“…Furthermore, elegant transplantation experiments in hamsters showed that this structure was indeed sufficient to drive behavioural rhythms: animals in which the SCN was ablated and that then received a SCN transplant showed restored rhythms [3]. When the transplant was derived from a mutant hamster strain that had a shorter endogenous period [4], the transplanted animals showed locomotor A c c e p t e d M a n u s c r i p t activity with the mutant period [3]. The SCN sends projections to a number of brain targets where its rhythmical electrical activity interacts with neural networks governing various outputs.…”
Section: The Central Clock In the Brainmentioning
confidence: 99%